ETIKA SAINS DALAM PERSPEKTIF SPIRITUALITAS ISLAM - Takdir, Mohammad (Khazanah: Jurnal Studi Islam dan Humaniora, 2017)
This paper aims to explore the idea of the importance science ethics in the Islamic spirituality perspectives. This study used library research to determine the ethical dimension of Islamic science which is more concerned with the benefit of the people rather than the negative impact of the development of science and technology. By using the view of Islamic spirituality, the development of modern science should be guided by ethics and morals that represent esoteric wisdom as the heart of religion.This study shows that the ethics of science in the view of Islamic spirituality always emphasizes the dimensions of wisdom as reflected in the use of science without neglecting the most basic human values. The ethics of science contained in Islamic spirituality is a reflection of the esoteric dimension that encourages its people to be more sensitive to the future of nature which becomes the most beautiful representation of God's face. The ethical-esoteric dimension inherent in Islamic science is expected to be implemented by religious people to better appreciate the universe as God's creation.